Spectrophotometric Determination of Certain Cephalosporins - Jane, J.; Subrahmanyam, E.V.S.; Sathyanarayana, D. (Asian Journal of Chemistry, 2010)
A simple and specific method for the quantitative determination of cephalosporins, namely ceftriaxone, cefoperazone, cefazidime and ceftizoxime was developed. The method was based on the formation of a blue coloured chromogen, when the drug solutions react with Folin-Ciocalteau reagent in an alkaline medium.